Avalanche breakdown and quenching in Ge SPAD using 3D Monte Carlo simulation. (August 2022) - Dollfus, P.; Saint-Martin, J.; Cazimajou, T.; Helleboid, R.; Pilotto, A.; Rideau, D.; Bournel, A.; Pala, M.
Highlights: We have analyzed the statistical behavior of a Ge SPAD using 3D self-consistent Monte Carlo simulation and shown in particular the probabilistic character of the quenching operation. The quenching resistance has a strong effect on the quenching probability that can rapidly switch from 0 to 100% according to this parameter. The effect of the quenching capacitance is more subtle due to the competition between two antagonistic phenomena (excess charge and discharge time) that makes its quantitative influence difficult to predict in the case of intermediate values of quenching resistance. The 3D Monte Carlo method appears to be very convenient to capture the effects of all stochastic ingredients of SPAD operation. Abstract: A Ge-based single-photon-avalanche-diode (SPAD) is investigated by using self-consistent 3-D Monte Carlo simulation including the presence of a passive quenching circuit. This approach of transport allows us to capture all stochastic features of carrier transport and SPAD operation. We analyze particularly the probabilistic character of the quenching mechanism and its dependence on the parameters (resistance and capacitance) of the passive quenching circuit.